Interactions of the SH2-domains of P13-kinase in activated T lineage cells - Strydom, Carolie M (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Sc.(Medical Biochemistry)) -- University of Stellenbosch, 1994.